Genotyping of Candida albicans and Candida dubliniensis by 25S rDNA analysis shows association with virulence attributes in oral candidiasis - Tantivitayakul, Pornpen; Panpradit, Naruemon; Maudcheingka, Thaniya; Klaophimai, Arthit; Lapirattanakul, Jinthana (Archives of oral biology, 2019)
•C. albicans genotypes A, B, C and D (C. dubliniensis) were identified.•Genotype B was the most prevalent in both healthy and candidiasis groups.•Genotype B showed highest adherence, but lowest phospholipase among C. albicans.•Genotype C C. albicans was more frequently detected in oral candidiasis patients.•Genotype D, the least prevalent, was more frequent in carriers and showed minimal virulence. This study genotyped oral isolates of Candida albicans and C. dubliniensis by analyzing 25S rDNA transposable intron and evaluated their virulence attributes in oral candidiasis. C. albicans and C. dubliniensis were isolated from oral cavity of normal carriers (n = 100) and oral candidiasis patients (n = 100), genotyped by PCR, and virulence properties, namely, secreted phospholipase and proteinase activities (using an agar plate method) and binding to buccal epithelial cells, were determined. In addition, antifungal sensitivity was assayed for all Candida isolates. C. albicans genotypes A, B, C and D (C. dubliniensis) were identified. Genotype B was the most prevalent in both healthy and candidiasis groups and had highest buccal epithelial cell binding ability but lowest secreted phospholipase activity. Genotype C was the third most prevalent, with higher frequency in patients than normal carriers. Genotype A, the second most prevalent, was equally found in both groups. There were no significant differences in secreted proteinase activity among the three C. albicans genotypes. C. dubliniensis, the least prevalent, was more frequent in healthy carriers and demonstrated minimal levels of the virulence properties. When all Candida isolates were compared based on groups of subjects, only secreted phospholipase activity was significantly higher in isolates from candidiasis patients. All Candida isolates were susceptible to clotrimazole, fluconazole, miconazole and nystatin. Genotyping based on the 25S rDNA transposable intron region provided a simple method allowing studies of the pathogenicity of each genotype.